A 10-Year Experience in Intraoperative Parathyroid Hormone Measurements for Primary Hyperparathyroidism: A Prospective Study of 91 Previous Unexplored Patients. (23rd February 2012) - Neves, M. C.; Ohe, M. N.; Rosano, M.; Abrahão, M.; Cervantes, O.; Lazaretti-Castro, M.; Vieira, J. G. H.; Kunii, I. S.; Santos, R. O.
Abstract : Introduction . Primary hyperparathyroidism (PHP) is characteristically determined by high levels of calcium and high or inappropriate levels of parathyroid hormone (PTH). Technological advances have dramatically changed the surgical technique over the years once intraoperative parathyroid hormone (IOPTH) assay had allowed for focused approaches. Objective . To evaluate our 10-year experience in employing a rapid intraoperative PTH assay for PHP. Methods . A prospective cohort of 91 PHP-operated patients in a tertiary institution in São Paulo, Brazil, from June 2000 to April 2011. Results . We had 85 (93.4%) successful parathyroidectomies, 6 (6.6%) failed parathyroidectomies in 91 previous unexplored patients, and 5 (100%) successful remedial surgeries. The IOPTH was true-positive in 88.5%, true-negative in 7.3%, false-positive in 2.1%, and false-negative in 2.1% of the procedures. IOPTH was able to obviate additional exploration or to ask for additional exploration in 92 (95.8%) procedures. Conclusion . The IOPTH revealed to be an important technological adjunct in the current parathyroid surgery for PHP.